Effect of Different Feeding Regimes on Nutrient Digestibility and Nutritive Value in Lactating Punganur Cows - Chandra Mouli Ambati (Indian Journal of Animal Nutrition, 2024)
Present experiment was conducted to study the effect of different feeding methods on nutrient digestibility and nutritive value in lactating Punganur cows.  In a completely randomized design (CRD) Sixteen lactating Punganur cows randomly assigned to four treatments with each group containing four animals into four treatment groups. Animals of T1 (Control) group were maintained as per the feeding practice followed by the farmers rearing Punganur cows in Chittoor district (Hedge lucerne + PS + CM), T2 group fed with Super Napier grass + PS + CM, T3 group fed with PS + CM + UMMB and T4 group fed with TMR. Results indicated that the digestibility (%) of DM and OM was highest in T3 when compared with T1, T2 and T4 groups, while the digestibility of other nutrients did not indicate any difference among the treatment groups. The Plane of nutrition indicated DMI (Kg/d) was significantly (P